2016
DOI: 10.1080/01635581.2016.1154577
|View full text |Cite
|
Sign up to set email alerts
|

Young Barley Indicates Antitumor Effects in Experimental Breast Cancer In Vivo and In Vitro

Abstract: The effect of dietary administered young barley containing a mixture of phytochemicals to female rats for the prevention of N-methyl-N-nitrosourea-induced mammary carcinogenesis was evaluated. After carcinogen administration (14 wk), mammary tumors were removed and prepared for histopathological and immunohistochemical analysis. Moreover, in vitro evaluation of possible mechanisms in MCF-7 breast cancer cell line was performed. Barley (0.3%) demonstrated mild antitumor effect in mammary carcinogenesis, yet 3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 38 publications
9
42
0
1
Order By: Relevance
“…The expression of Ki67 is rigorously associated with the cell cycle progression . In this study, the decrease in Ki67 expression in rat mammary carcinomas is in accordance with our earlier results testing different plant functional foods . Our in vitro study (MTS and BrdU assays and analysis of cell cycle) confirmed antiproliferative effects of CLOs in breast adenocarcinoma cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The expression of Ki67 is rigorously associated with the cell cycle progression . In this study, the decrease in Ki67 expression in rat mammary carcinomas is in accordance with our earlier results testing different plant functional foods . Our in vitro study (MTS and BrdU assays and analysis of cell cycle) confirmed antiproliferative effects of CLOs in breast adenocarcinoma cells.…”
Section: Discussionsupporting
confidence: 92%
“…Free radicals that damage important cell macromolecules play a substantial role in the etiopathogenesis of cancer . Recently, we have found that dietary administered young barley, rich in antioxidants (flavonoids), apparently lowered the levels of dityrosines in mammary cancer cells in rats . MDA is often used as a marker of the oxidative damage of lipids by free radicals .…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of cancer cell cycle progression is very often described as one of the mechanisms of anticancer action. Such an activity of young barley was described by Kubatka in MCF-7 breast cancer cells [27]. In the presented study, no significant changes were observed in the HT-29 and A549 cells cell cycle progression after exposure to the HWE extract (Tab.…”
Section: Resultssupporting
confidence: 66%
“…Recently, the antiproliferative potential of young barley extracts has been revealed in breast cancer cells [27]. In the study by Kubatka et al, the tested barley extract at the concentration 1 mg/ml decreased MCF-7 breast cancer cells proliferation to 37.93% after 72 h treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Plant-derived bioactive molecules (phytochemicals) are of particular interest within oncological research. Numerous phytochemicals or natural mixtures of plant compounds present in whole foods show significant antitumor properties via multiple cell signaling pathways and mechanisms, and thus, represent perspective and potentially effective tools for chemoprevention and targeted therapy of cancer disease [14,30,[169][170][171][172]. Moreover, an administration of dietary phytochemicals is the way of a cost-effective and readily applicable clinical approach in the management of cancer, including the most commonly occurring BC, PC, and CRC.…”
Section: Discussionmentioning
confidence: 99%